Obestatin Reduces Intestinal Damage in Experimental Necrotizing Enterocolitis in Newborn Rats - Korkut, Sabriye; Özdemir, Ahmet; Yay, Arzu Hanım; Yalçın, Betül; Ceylan, Mahir; Korkmaz, Levent; Yazıcı, Cevat; Güntürk, İnayet; Kurtoğlu, Selim (American Journal of Perinatology, 2019)
Objective To investigate the effect of pretreatment with obestatin (OB), an endogenous hormone also found in mother's milk, in experimental necrotizing enterocolitis (NEC).Study Design Pups were randomized into four groups: control, OB-control, NEC, and OB-NEC. NEC was induced by asphyxia and hypothermia in the NEC and OB-NEC groups. OB was administered to the OB-control and OB-NEC groups. Macroscopic scoring of the intestinal tract was evaluated and tissue samples were obtained for histopathological and biochemical examination on the fourth day.Results OB improved the macroscopic appearance of the gut and the clinical score during the experiment (p  <  0.05). The rate of occurrence of NEC in the OB-NEC group was lower than the NEC group (p  =  0.001). OB prevented necrosis and reduced the number of apoptotic cells in the OB-NEC group compared with the NEC group (p  =  0.006). Furthermore, interleukin-6 and malondialdehyde levels in the OB-NEC group were lower than the NEC group (p  <  0.05).Conclusion OB reduced intestinal damage and prevented necrosis through anti-inflammatory and antiapoptotic effects in experimental NEC. This effect of OB should be confirmed in clinical studies. Furthermore, future research should investigate whether OB plays a role in NEC pathogenesis or NEC is associated with OB levels in the serum and in breast milk.
Keywords: necrotizing enterocolitis; obestatin; treatment; rat; newborn